2005
DOI: 10.1007/s10969-005-1918-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Limited Proteolysis/Mass Spectrometry for Protein Domain Elucidation

Abstract: High-resolution structural information is important for improving our understanding of protein function in vitro and in vivo and providing information to enable drug discovery. The process leading to X-ray structure determination is often time consuming and labor intensive. It requires informed decisions in expression construct design, expression host selection, and strategies for protein purification, crystallization and structure determination. Previously published studies have demonstrated that compact glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 14 publications
0
47
0
Order By: Relevance
“…We have found that if a clear mass spectrum was obtained on an intact target protein, its proteolytic fragments were also measured reliably and the current method was applicable. Because this method identifies flexible and stable regions of proteins, it is useful in the design of protein constructs for X-ray crystallography studies [29], as well as for studying proteins with unknown structures. It is also conceivable that when a high-resolution mass spectrometer such as Fourier transform mass spectrometer (FTMS) is used, this method can be applied to much larger proteins, since the corresponding mass window for selecting potential subsequences can be significantly reduced for FTMS.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that if a clear mass spectrum was obtained on an intact target protein, its proteolytic fragments were also measured reliably and the current method was applicable. Because this method identifies flexible and stable regions of proteins, it is useful in the design of protein constructs for X-ray crystallography studies [29], as well as for studying proteins with unknown structures. It is also conceivable that when a high-resolution mass spectrometer such as Fourier transform mass spectrometer (FTMS) is used, this method can be applied to much larger proteins, since the corresponding mass window for selecting potential subsequences can be significantly reduced for FTMS.…”
Section: Discussionmentioning
confidence: 99%
“…If full length protein is available, limited proteolysis combined with mass spectrometric (MS) approaches can determine core folded domains, as connecting unfolded sequence or disordered termini may be trimmed away by proteases, with core domains identified by MS [40]. In addition, the advent of powerful high-throughput screening of random or combinatorial protein truncation or mutation libraries allows an unbiased approach with no prior knowledge required [41].…”
Section: Further Methods For Domain Boundary Analysis: Beyond Bioinfomentioning
confidence: 99%
“…against protein domains of known structure), disorder predictions, and secondary structure predictions (Mooij et al, 2009). In silico analysis of the target can be complemented by experimental methods, such as partial proteolysis (Gao et al, 2005).…”
Section: Engineering Proteins For Structural Studies: Construct Desigmentioning
confidence: 99%